Bimetal oxygen evolution pre-catalyst material based on metal organic framework as well as preparation method and application of bimetal oxygen evolution pre-catalyst material
By growing metal organic frame nanoarrays on foam nickel substrates and introducing metal sources to prepare bimetallic oxygen evolution precatalyst materials, the existing catalysts have been solved, with low activity, poor stability and high cost, and high efficiency, low cost and stable catalyst performance have been achieved.
Patent Information
- Application Number
- CN202510039377.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
AI Technical Summary
The existing catalysts have insufficient activity, poor stability and high cost in hydrogen preparation, making it difficult to meet the needs of efficient, low-cost and stable catalysts.
Bimetallic oxygen evolution precatalyst material is prepared by wet chemistry by growing metal organic frame nanoarrays on a foam nickel substrate and introducing a metal source.
It improves the activity of electrocatalytic oxygen evolution reaction, the material is simple and easy to operate, low cost, suitable for mass production, and shows excellent stability under high temperature and long-term testing.
Smart Images

Figure CN119800439A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and specifically relates to a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework, a preparation method and an application thereof. Background Art
[0002] With the rapid development of the global economy, the demand for energy is increasing. Traditional fossil fuels (such as coal, oil and natural gas) dominate the energy supply, but they are non-renewable resources and have caused a series of serious environmental problems. The energy crisis has become one of the major challenges facing the world, and there is an urgent need to find sustainable clean energy alternatives. Hydrogen energy, as a clean energy with great potential, has received widespread attention. As a clean energy, hydrogen has unique advantages in energy storage and conversion. It can be applied to fuel cell vehicles, distributed power generation, energy storage systems and other fields, and is regarded as an important part of the future energy system. However, the widespread application of hydrogen energy faces some key technical difficulties. For example, in the preparation of hydrogen, the production of hydrogen by water decomposition is a sustainable method, but the reaction usually requires high energy input and has a slow reaction rate. Efficient catalysts can reduce the activation energy of the reaction, increase the reaction rate, and thus reduce the cost of hydrogen production. At present, although some catalysts have been used in hydrogen energy-related fields, they often have problems such as low activity, poor stability and high cost. Therefore, the development of high-performance, low-cost and stable catalysts is the key to promoting the development of hydrogen energy technology and realizing the widespread application of hydrogen energy.
[0003] Metal-organic frameworks (MOFs) are a very important class of materials with a wide range of applications in the field of electrocatalysis, especially in important electrocatalytic reactions such as water splitting, oxygen reduction reaction, oxygen evolution reaction (OER) and hydrogen evolution reaction. The catalytic performance of metal-organic framework materials can be further improved by further optimizing the MOF structure and electronic coupling through interface engineering design. Pre-electrocatalytic materials formed through techniques such as interface engineering and atomic doping show unique advantages in performance and are expected to play a greater role in future clean energy technologies. Summary of the invention
[0004] In view of the above problems, the present invention proposes a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework, a preparation method and an application thereof. The idea is to grow a metal organic framework nanoarray on a nickel foam substrate, introduce a metal source on the basis thereof, and prepare an efficient OER pre-catalyst simply and quickly by a wet chemical method. By adjusting the MOF components in the preparation process and exploring and optimizing a series of reaction conditions, the problems of high cost and low catalytic efficiency of traditional precious metal catalysts are solved.
[0005] In the first aspect, the present invention proposes a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework, comprising an organic metal framework nanoarray, the organic metal framework nanoarray comprises a foam nickel substrate, the surface of the foam nickel substrate is evenly distributed with dicarboxylic acid organic ligands and divalent transition metal salts, the dicarboxylic acid organic ligands are coordinated with metal ions in the divalent transition metal salts through carboxyl groups to form a stable metal organic framework structure; wherein the divalent transition metal ions are coordinated with iron ions through metal-metal bonds.
[0006] Preferably, the divalent transition metal salt is one of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, nickel nitrate, nickel acetate, nickel chloride, nickel sulfate, copper nitrate, copper acetate, copper chloride, copper sulfate, manganese nitrate, manganese acetate, manganese chloride, manganese sulfate, zinc nitrate, zinc acetate, zinc chloride and zinc sulfate.
[0007] Preferably, the dicarboxylic acid organic ligand is one of 2,6-naphthalene dicarboxylic acid, 1,4-terephthalic acid, 4,4'-biphenyl dicarboxylic acid, 2-hydroxyterephthalic acid, 2-methyl-1,4-terephthalic acid, p-mercaptoterephthalic acid and 2,5-dicarboxyfluorobenzene.
[0008] Preferably, the shape of the nickel foam substrate is a cuboid with a length of 15 mm, a width of 15 mm and a height of 1.5 mm.
[0009] In a second aspect, the present invention provides a method for preparing a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework, the steps of which include:
[0010] A1. dropping an aqueous solution containing a divalent transition metal salt into an N,N-dimethylformamide solution containing a dicarboxylic acid organic ligand; the amount of the divalent transition metal salt contained in the aqueous solution of the divalent transition metal salt to the amount of the dicarboxylic acid organic ligand contained in the N,N-dimethylformamide solution is 1:0.5-3; the concentration of the aqueous solution of the divalent transition metal salt is 20-100 mg / mL; the concentration of the N,N-dimethylformamide solution of the dicarboxylic acid organic ligand is 1-20 mg / mL, and the ethanol is 1-10 mL;
[0011] A2. After mixing, ethanol was added dropwise to obtain a mixed solution, and the nickel foam was vertically immersed in the mixed solution, and the reaction was carried out in a reactor at 60°C-180°C under sealed conditions for 8-72h;
[0012] A3. The obtained nickel foams were sequentially treated and washed and dried to obtain MOF nanoarrays loaded on nickel foams;
[0013] A4. The MOF nanoarray prepared in step A3 is placed in a ferric chloride solution and reacted at 50-150°C for 20min-72h; the concentration of the ferric chloride solution is 0.01-0.2M;
[0014] A5. The nickel foam produced in A4 is cleaned and dried to obtain a finished product.
[0015] Preferably, in step A2, the nickel foam is pretreated before being immersed in the mixed solution, and the pretreatment steps include: ultrasonic cleaning with 0.02-10M hydrochloric acid, acetone, ultrapure water, and ethanol as washing solutions in sequence, rinsing with ultrapure water before each change of the washing solution, and finally drying in an oven.
[0016] Preferably, the solute of the aqueous solution of the divalent transition metal salt in step A1 is one of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, nickel nitrate, nickel acetate, nickel chloride, nickel sulfate, copper nitrate, copper acetate, copper chloride, copper sulfate, manganese nitrate, manganese acetate, manganese chloride, manganese sulfate, zinc nitrate, zinc acetate, zinc chloride and zinc sulfate.
[0017] Preferably, the solvent of the ferric chloride solution in step A4 is one of 1-propanol, water, ethanol and acetonitrile.
[0018] Preferably, after the nickel foam is dried in step A5, the nickel foam is immersed in 1M KOH and electrochemically reconstructed at a voltage of 100 mV for 12 hours.
[0019] In a third aspect, the present invention proposes an application of a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework in an electrocatalytic reaction, including an electrocatalytic oxygen evolution reaction and its application in alkaline water electrolysis.
[0020] The beneficial effects of the present invention are: uniform and clear-shaped MOFNA is grown on nickel foam, and iron atoms are introduced on the surface of the nanosheets without destroying the internal structure of the nanosheets, and a wet chemical reaction is performed to form a bimetallic oxygen evolution precatalyst material, thereby improving the activity of the electrocatalytic oxygen evolution reaction. The method of the present invention is simple and easy to operate, low in cost, and can be mass-produced;
[0021] Compared with the closest prior art with publication number CN116078438B, the material of the present invention is simpler to prepare, has a wider range of raw material choices, has better performance, and also exhibits excellent stability under high temperature and long-term testing, and is suitable for large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of CoFe-MOFNA, a bimetallic oxygen evolution precatalyst material based on a metal organic framework of the present invention.
[0023] Figure 2 It is a scanning electron microscope image of the NiFe-MOFNA of the present invention.
[0024] Figure 3It is a scanning electron microscope image of the CuFe-MOFNA of the present invention.
[0025] Figure 4 It is a scanning electron microscope image of the NiFe-MOF(OH)NA of the present invention.
[0026] Figure 5 It is a scanning electron microscope image of the NiFe-MOF(CH3)NA of the present invention.
[0027] Figure 6 1 is the XRD pattern of five MOFNAs of the present invention.
[0028] Figure 7 Linear sweep voltammetry curves of the electrocatalytic oxygen evolution reaction of the five MOFNAs of the present invention.
[0029] Figure 8 It is a polarization curve diagram of NiFe-MOFNA of the present invention at different temperatures. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0031] Embodiment 1
[0032] Take 1.5mm thick nickel foam (NF) and cut it into 2.3×3cm 2Size. In order to remove oxides and grease on the surface of NF and enable Ni-MOF to grow evenly on the substrate, 3M hydrochloric acid solution, acetone, ultrapure water and ethanol were used for ultrasonic cleaning for 15 minutes respectively, and ultrapure water was used to rinse three times before each solution change. Take 108.5mg of Co(NO3)2·6H2O in a centrifuge tube, add 1mL of ultrapure water and mix evenly by ultrasonic; take 62mg of 1,4-terephthalic acid (0.373mmol) in a centrifuge tube, add 16mL of N,N-dimethylformamide solution, and disperse evenly by ultrasonic. Add Co(NO3)2·6H2O solution dropwise to the N,N-dimethylformamide solution containing 1,4-terephthalic acid, and transfer it to the inner tank of a 25mL polymerization reactor. Place the cleaned NF vertically, seal it and place it in an oven, react at 120°C for 12 hours; after the reaction is completed, cool it to room temperature, wash the obtained sample with ultrapure water, ultrasonicate for 60 seconds, and dry it at 60°C overnight to obtain the original metal organic framework nanoarray. Take 405.5 mg of anhydrous ferric chloride on a balance, add 100 mL of 1-propanol solution, and ultrasonicate for 60 seconds to disperse it as evenly as possible; take 5 mL of ferric chloride solution in a glass reaction bottle, put the obtained original metal organic framework nanoarray into the solution, and react at 80°C for 12 hours; after cooling to room temperature, wash the obtained sample with ultrapure water and ultrasonicate for 60 seconds, and dry it at 60°C overnight to obtain the metal organic framework-based bimetallic oxygen evolution pre-catalyst material CoFe-MOFNA. Its scanning electron microscope image is as follows Figure 1 shown.
[0033] Embodiment 2
[0034] Take 1.5mm thick nickel foam (NF) and cut it into 2.3×3cm 2Size. In order to remove oxides and grease on the surface of NF and enable Ni-MOF to grow evenly on the substrate, 3M hydrochloric acid solution, acetone, ultrapure water and ethanol were used for ultrasonic cleaning for 15 minutes respectively, and ultrapure water was used to rinse three times before each solution change. Take 55mg NiCl2·6H2O in a centrifuge tube, add 1mL ultrapure water and mix evenly by ultrasonic; take 62mg 1,4-terephthalic acid (0.373mmol) in a centrifuge tube, add 16mL N,N-dimethylformamide solution, and disperse evenly by ultrasonic. Add Co(NO3)2·6H2O solution dropwise to the N,N-dimethylformamide solution containing 1,4-terephthalic acid, and transfer it to the inner tank of a 25mL polymerization reactor. Put the cleaned NF vertically, seal it and place it in an oven to react at 120℃ for 12h; after the reaction, cool it to room temperature, wash the obtained sample with ultrapure water, ultrasonic for 60s, and dry it at 60℃ overnight to obtain the original metal organic framework nanoarray. Take 405.5mg of anhydrous ferric chloride on a balance, add 100mL of 1-propanol solution, and ultrasonicate for 60s to disperse it as evenly as possible; take 5mL of ferric chloride solution in a glass reaction bottle, put the prepared original metal organic framework nanoarray into the solution, and react at 80℃ for 12h; after cooling to room temperature, wash the obtained sample with ultrapure water and ultrasonicate for 60s, and dry it at 60℃ overnight to obtain the bimetallic oxygen evolution pre-catalyst material NiFe-MOFNA based on metal organic framework. Its scanning electron microscope image is as follows Figure 2 shown.
[0035] Embodiment 3
[0036] Take 1.5mm thick nickel foam (NF) and cut it into 2.3×3cm 2Size. In order to remove oxides and grease on the surface of NF and enable Ni-MOF to grow evenly on the substrate, 3M hydrochloric acid solution, acetone, ultrapure water and ethanol were used for ultrasonic cleaning for 15 minutes respectively, and ultrapure water was used to rinse three times before each solution change. Take 63.5mg CuCl2·2H2O in a centrifuge tube, add 1mL ultrapure water and mix evenly by ultrasonic; take 62mg 1,4-terephthalic acid (0.373mmol) in a centrifuge tube, add 16mL N,N-dimethylformamide solution, and disperse evenly by ultrasonic. Add Co(NO3)2·6H2O solution dropwise to the N,N-dimethylformamide solution containing 1,4-terephthalic acid, and transfer it to the inner tank of a 25mL polymerization reactor. Place the cleaned NF vertically, seal it and place it in an oven, react at 120°C for 12 hours; after the reaction is completed, cool it to room temperature, wash the obtained sample with ultrapure water, ultrasonicate for 60 seconds, and dry it at 60°C overnight to obtain the original metal organic framework nanoarray. Take 405.5 mg of anhydrous ferric chloride on a balance, add 100 mL of 1-propanol solution, and ultrasonicate for 60 seconds to disperse it as evenly as possible; take 5 mL of ferric chloride solution in a glass reaction bottle, put the obtained original metal organic framework nanoarray into the solution, and react at 80°C for 12 hours; after cooling to room temperature, wash the obtained sample with ultrapure water and ultrasonicate for 60 seconds, and dry it at 60°C overnight to obtain the bimetallic oxygen evolution pre-catalyst material CuFe-MOFNA based on the metal organic framework. Its scanning electron microscope image is as follows Figure 3 shown.
[0037] Embodiment 4
[0038] Take 1.5mm thick nickel foam (NF) and cut it into 2.3×3cm 2Size. In order to remove oxides and grease on the surface of NF and enable Ni-MOF to grow evenly on the substrate, 3M hydrochloric acid solution, acetone, ultrapure water and ethanol were used for ultrasonic cleaning for 15 minutes respectively, and ultrapure water was used to rinse three times before each solution change. Take 55mg NiCl2·6H2O in a centrifuge tube, add 1mL ultrapure water and mix evenly by ultrasonication; take 68mg 2-hydroxyterephthalic acid (0.373mmol) in a centrifuge tube, add 16mL N,N-dimethylformamide solution, and disperse evenly by ultrasonication. Add Co(NO3)2·6H2O solution dropwise to the N,N-dimethylformamide solution containing 2-hydroxyterephthalic acid, and transfer it to the inner tank of a 25mL polymerization reactor. Put the cleaned NF vertically, seal it and place it in an oven to react at 120℃ for 12h; after the reaction is completed, cool it to room temperature, wash the obtained sample with ultrapure water, ultrasonicate for 60s, and dry it at 60℃ overnight to obtain the original metal organic framework nanoarray. Take 405.5mg of anhydrous ferric chloride on a balance, add 100mL of 1-propanol solution, and ultrasonicate for 60s to make it as evenly dispersed as possible; take 5mL of ferric chloride solution in a glass reaction bottle, put the prepared original metal organic framework nanoarray into the solution, and react at 80℃ for 12h; after cooling to room temperature, wash the obtained sample with ultrapure water and ultrasonicate for 60s, and dry it at 60℃ overnight to obtain the bimetallic oxygen evolution precatalyst material NiFe-MOF(OH)NA based on metal organic framework. Its scanning electron microscope image is as follows Figure 4 shown.
[0039] Embodiment 5
[0040] Take 1.5mm thick nickel foam (NF) and cut it into 2.3×3cm 2Size. In order to remove oxides and grease on the surface of NF and enable Ni-MOF to grow evenly on the substrate, 3M hydrochloric acid solution, acetone, ultrapure water and ethanol were used for ultrasonic cleaning for 15 minutes respectively, and ultrapure water was used to rinse three times before each solution change. Take 55mg NiCl2·6H2O in a centrifuge tube, add 1mL ultrapure water and mix evenly by ultrasonic; take 62mg 2-methyl-1,4-terephthalic acid (0.373mmol) in a centrifuge tube, add 16mL N,N-dimethylformamide solution, and disperse evenly by ultrasonic. Add Co(NO3)2·6H2O solution dropwise to the N,N-dimethylformamide solution containing 2-methyl-1,4-terephthalic acid, and transfer it to the inner tank of a 25mL polymerization reactor. Place the cleaned NF vertically, seal it and place it in an oven, react at 120°C for 12 hours; after the reaction is completed, cool it to room temperature, wash the obtained sample with ultrapure water, ultrasonicate for 60 seconds, and dry it at 60°C overnight to obtain the original metal organic framework nanoarray. Take 405.5 mg of anhydrous ferric chloride on a balance, add 100 mL of 1-propanol solution, and ultrasonicate for 60 seconds to disperse it as evenly as possible; take 5 mL of ferric chloride solution in a glass reaction bottle, put the obtained original metal organic framework nanoarray into the solution, and react at 80°C for 12 hours; after cooling to room temperature, wash the obtained sample with ultrapure water and ultrasonicate for 60 seconds, and dry it at 60°C overnight to obtain the bimetallic oxygen evolution pre-catalyst material NiFe-MOF(CH3)NA based on the metal organic framework. Its scanning electron microscope image is as follows Figure 5 shown.
[0041] Figure 6 : This is the XRD spectrum of the five MOFNAs in Examples 1, 2, 3, 4 and 5. It can be seen from the figure that an obvious MOF diffraction peak can be seen at 8.5°.
[0042] Figure 7 The linear sweep voltammetric curves of the five MOFNAs in Examples 1, 2, 3, 4, and 5 are shown in Figure 1, among which NiFe-MOFNA has the best performance at 10 mA cm -2 At a current density of , the overpotential only needs to be 196mV.
[0043] Figure 8 This is a polarization curve diagram of NiFe-MOFNA prepared in Example 2 at different temperatures. As the temperature continues to rise, the current density gradually increases and the overpotential decreases, showing excellent electrochemical activity at high temperatures.
[0044] The present invention discloses a preparation method of a bimetallic oxygen evolution precatalyst based on a metal organic framework grown on a nickel foam substrate; the preparation method of the material is: introducing a metal source into a metal organic framework nanoarray on the nickel foam and performing electrochemical reconstruction, thereby forming a bimetallic oxygen evolution precatalyst material while retaining the morphology of the original MOF nanoarray. The present invention introduces a metal source into the metal organic framework nanoarray by a wet chemical method to form a bimetallic oxygen evolution precatalyst material, thereby solving the problems of complex synthesis and low activity of traditional oxygen evolution catalysts. The prepared material is low in price, simple to synthesize, and has excellent electrocatalytic activity and long-term stability at both room temperature and high temperature. The electrocatalytic activity is 10 mA cm -2 At a current density of , the overpotential only needs to be 196mV.
Claims
1. A bimetallic oxygen evolution pre-catalyst material based on a metal organic framework, characterized in that: The organic metal framework nanoarray comprises a nickel foam substrate, on the surface of which dicarboxylic acid organic ligands and divalent transition metal salts are evenly distributed, and the dicarboxylic acid organic ligands coordinate with metal ions in the divalent transition metal salts through carboxyl groups to form a stable metal organic framework structure; wherein the divalent transition metal ions coordinate with iron ions through metal-metal bonds.
2. A bimetallic oxygen evolution pre-catalyst material based on a metal organic framework according to claim 1, characterized in that: The divalent transition metal salt is one of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, nickel nitrate, nickel acetate, nickel chloride, nickel sulfate, copper nitrate, copper acetate, copper chloride, copper sulfate, manganese nitrate, manganese acetate, manganese chloride, manganese sulfate, zinc nitrate, zinc acetate, zinc chloride and zinc sulfate.
3. The bimetallic oxygen evolution pre-catalyst material based on a metal organic framework according to claim 1, characterized in that: The dicarboxylic acid organic ligand is one of 2,6-naphthalene dicarboxylic acid, 1,4-terephthalic acid, 4,4'-biphenyl dicarboxylic acid, 2-hydroxyterephthalic acid, 2-methyl-1,4-terephthalic acid, p-mercaptoterephthalic acid and 2,5-dicarboxyfluorobenzene.
4. The bimetallic oxygen evolution pre-catalyst material based on a metal organic framework according to claim 1, characterized in that: The shape of the nickel foam substrate is a cuboid with a length of 15 mm, a width of 15 mm, and a height of 1.5 mm.
5. The method for preparing a bimetallic oxygen evolution precatalyst material based on a metal organic framework according to claim 1, comprising the steps of: A1. dropping an aqueous solution containing a divalent transition metal salt into an N,N-dimethylformamide solution containing a dicarboxylic acid organic ligand; the amount of the divalent transition metal salt contained in the aqueous solution of the divalent transition metal salt to the amount of the dicarboxylic acid organic ligand contained in the N,N-dimethylformamide solution is 1:0.5-3; the concentration of the aqueous solution of the divalent transition metal salt is 20-100 mg / mL; the concentration of the N,N-dimethylformamide solution of the dicarboxylic acid organic ligand is 1-20 mg / mL, and the ethanol is 1-10 mL; A2. After mixing, ethanol was added dropwise to obtain a mixed solution, and the nickel foam was vertically immersed in the mixed solution, and the reaction was carried out in a reactor at 60°C-180°C under sealed conditions for 8-72h; A3. The obtained nickel foams were sequentially treated and washed and dried to obtain MOF nanoarrays loaded on nickel foams; A4. The MOF nanoarray prepared in step A3 is placed in a ferric chloride solution and reacted at 50-150°C for 20min-72h; the concentration of the ferric chloride solution is 0.01-0.2M; A5. The nickel foam produced in A4 is cleaned and dried to obtain a finished product.
6. The method for preparing a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework according to claim 5, characterized in that: In step A2, the nickel foam is pretreated before being immersed in the mixed solution. The pretreatment steps include: ultrasonic cleaning with 0.02-10M hydrochloric acid, acetone, ultrapure water, and ethanol as washing solutions in sequence, rinsing with ultrapure water before each change of washing solution, and finally drying in an oven.
7. The method for preparing a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework according to claim 5, characterized in that: The solute of the aqueous solution of the divalent transition metal salt in step A1 is one of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, nickel nitrate, nickel acetate, nickel chloride, nickel sulfate, copper nitrate, copper acetate, copper chloride, copper sulfate, manganese nitrate, manganese acetate, manganese chloride, manganese sulfate, zinc nitrate, zinc acetate, zinc chloride and zinc sulfate.
8. The method for preparing a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework according to claim 5, characterized in that: The solvent of the ferric chloride solution in step A4 is one of 1-propanol, water, ethanol and acetonitrile.
9. The method for preparing a bimetallic oxygen evolution pre-catalyst material based on a metal organic framework according to claim 5, characterized in that: After the nickel foam is dried in step A5, it is immersed in 1M KOH and electrochemically reconstructed at a voltage of 100 mV for 12 h.
10. The use of a metal organic framework-based bimetallic oxygen evolution precatalyst material in an electrocatalytic reaction according to claim 1, comprising an electrocatalytic oxygen evolution reaction and its use in alkaline water electrolysis.
Citation Information
Patent Citations
Electrocatalytic materials based on iron oxyhydroxide and metal-organic frameworks
CN116078438B
Preparation method and application of metal-organic framework compound electrocatalyst
CN110975937A
Iron / tungsten bimetal organic framework anode oxygen evolution composite material and preparation method thereof
CN111790446A
Hollow metal organic framework-tannic acid-polypyrrole composite material as well as preparation method and application thereof
CN113512735A
Preparation and application of anode oxygen evolution catalyst with high-valence metal vanadium doped with CoFe-MOF / NF
CN116083954A